2021
DOI: 10.3390/toxins13070446
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Zearalenone and Its Metabolites in the Blood of High-Yielding Dairy Cows at Selected Collection Sites in Various Disease States

Abstract: Zearalenone (ZEN) and its metabolites, alpha-zearalenol (α-ZEL) and beta-zearalenol (β-ZEL), are ubiquitous in plant materials used as feed components in dairy cattle diets. The aim of this study was to confirm the occurrence of ZEN and its selected metabolites in blood samples collected from different sites in the hepatic portal system (posthepatic–external jugular vein EJV; prehepatic–abdominal subcutaneous vein ASV and median caudal vein MCV) of dairy cows diagnosed with mastitis, ovarian cysts and pyometra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
0
10
1
4
Order By: Relevance
“…At the end of the first study stage, not only ZEN metabolites, which were in the blood serum samples, but also other ZEN derivates, such as α-ZAL and β-ZAL, were detected in the urine samples. The obtained results differed from those published by Polish scientists [15], who maintained that α-ZEL and β-ZEL concentrations either were absent from the blood serum of cows or occurred in amounts below LOD.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…At the end of the first study stage, not only ZEN metabolites, which were in the blood serum samples, but also other ZEN derivates, such as α-ZAL and β-ZAL, were detected in the urine samples. The obtained results differed from those published by Polish scientists [15], who maintained that α-ZEL and β-ZEL concentrations either were absent from the blood serum of cows or occurred in amounts below LOD.…”
Section: Discussioncontrasting
confidence: 99%
“…The initial decomposition of mycotoxins begins in the rumen of a cow; the rumen microbiota is one of the factors necessary for the process to take place. Therefore, the concentration of ZEN and its metabolites can be more reliably quantified in blood, urine, and milk samples [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the contamination period had high percentages of cows which were categorized as having clinical metritis. Baranski et al (2021) also reported that uterine infection was correlated with blood ZEA concentrations in cows. It is suggested that the immunosuppressive effects of mycotoxins, as well as impaired metabolic status due to reducing DMI, may predispose the cows to uterine infections.…”
Section: Discussionmentioning
confidence: 93%
“…Мікотоксикоз є великою групою захворювань великої рогатої худоби та дрібних жуйних тварин, а також птахів, завдають великої економічної шкоди тваринництву (Sandmeyer et al, 2015;Barański et al, 2021).…”
Section: вступunclassified